2015
DOI: 10.5812/atr.25299v2
|View full text |Cite
|
Sign up to set email alerts
|

Routine Chest Computed Tomography and Hospital Admission Time and Complications in Patients with Blunt Trauma

Abstract: Background:Computerized Tomography (CT) scan is gaining more importance in the initial evaluation of patients with multiple trauma, but its effect on the outcome is still unclear. Until now, no prospective randomized trial has been performed to define the role of routine chest CT in patients with blunt trauma.Objectives:In view of the considerable radiation exposure and the high costs of CT scan, the aim of this study was to assess the effects of performing the routine chest CT on the outcome as well as compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…However, in their study the diagnosis of rib fractures did not result in differences of the length of hospital stay, intensive care unit (ICU) admission rate or in-hospital mortality, which was remarkably higher-by 10.3%-in patients with CT-detected rib fractures [10]. Further studies on blunt trauma patients of every age have demonstrated that chest XR misses rib fractures and relevant intrathoracic injuries in blunt trauma patients of every age [27][28][29]. The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, in their study the diagnosis of rib fractures did not result in differences of the length of hospital stay, intensive care unit (ICU) admission rate or in-hospital mortality, which was remarkably higher-by 10.3%-in patients with CT-detected rib fractures [10]. Further studies on blunt trauma patients of every age have demonstrated that chest XR misses rib fractures and relevant intrathoracic injuries in blunt trauma patients of every age [27][28][29]. The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27].…”
Section: Discussionmentioning
confidence: 88%
“…The proportion of undiagnosed rib fractures in chest XR ranges from 45% [29] to 74.5% (median three additional fractures in CT) [27]. Intrathoracic injuries have been CT-identified in 26% of the cases [28], leading to changes in clinical management in 8% [28], respectively 34.5% [27] of the cases. Additionally, it has been demonstrated that mortality increases by 19% with each additional rib fracture in older patients with blunt trauma [30].…”
Section: Discussionmentioning
confidence: 99%
“…This case illustrates how a low-dose contrast chest CT scan could be considered as a primary imagining tool in patients with suspected severe thoracic trauma such as a fall from heights. The decision to use an initial CT scan over chest radiography should always be made thoughtfully, considering benefits such as diagnosing occult life-threatening injuries as well as the disadvantages in terms of higher costs and radiation burden and the risk of overdiagnosis and overtreatment [ 7 ]. Most importantly CT chest should be the first choice if patients present with delayed complications after rib fractures, since chest radiography may miss a chest wall hematoma [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…При цьому 37,5 % цих пацієнтів потребували операції за життєвими показаннями [14]. КТ краще виявляє забиті місця легень, пневмоторакс, переломи ребер і травми великих судин, забезпечуючи 38-81 % додаткових діагнозів порівняно з рентгенографією грудної клітки [15].…”
Section: вступunclassified